Characteristics of PVA/GO Composite Membranes Prepared Using Solution Casting Technique for Reducing Methylene Blue Concentration - Fauziah Siti Ajizah; Fitrilawati, Ayi Bahtiar; Norman Syakir (JIIF (Jurnal Ilmu dan Inovasi Fisika), 2023)
In this study, the composite films of polyvinyl alcohol (PVA) and graphene oxide (GO) that referred as PVA/GO composites were prepared with a solution casting technique to be used as a filtration membrane. PVA/GO solution was prepared by mixing PVA powder, GO dispersion and aqueous solvent, then subjected to a hydrothermal process. The PVA/GO composite solution was cast on the glass substrate, then dried overnight so the solvent evaporated and then the composites films were removed from the substrate. The PVA/GO composite that characterized by SEM indicates that the GO is evenly dispersed within the PVA matrix. The FTIR spectrum of the composite has a sharp peak at 1655 cm-1 that associated with C=O and C=C bonds relating to GO characteristics. The TGA measurement results show that the PVA/GO composite film has better thermal stability than the PVA film. The PVA/GO composite films have been used as filtration membranes to reduce the concentration of methylene blue (MB) solutions contained in water. The filtration experiment that performed at various pressures showed that the permeability of the PVA/GO composite membranes was relatively constant at each pressure. Membrane permeability at pressures of 20 psi, 30 psi and 45 psi for PVA membranes are 1.95×10-3,  2.08×10-3 and 2.00×10-3 Darcy, while for PVA/GO composite membranes are 2.49×10-4, 1.22×10-3 and 2.23×10-3 Darcy